Quranic Forensic on Begging: Formulating Policies and Action Plans to Handle Street Beggars - Hanafi, Yusuf; Ikhsan, M. Alifudin; Diyana, Tsania Nur; Nurushofa, Zuroidah Zeni (LP2M - Universitas Islam Negeri (UIN) Walisongo, 2018)
Begging behavior is a serious issue and happens on a wide scale, especially in urban areas. In Islamic normative point of view, the Quran has a distinctive perspective towards beggars. In Sura al-Mā‘ūn [107]: 3, Allah swt. encourages Moslem people to pay attention to poor beggars. In contrast, in other verses, al-Jāthiyah [45]: 7, al-Quran criticizes people who are lying for the sake of other’s mercy with a mode and guise of a falsehood. In fact, the begging behavior nowadays is not only caused by the economic problem, but beggars even make it as a preferable profession. The biggest problem in handling the beggar issues is the difficulty to differentiate between the genuine and the professional beggar. If we examine thoroughly using an analysis of the Quran verses, there is a distinctive characteristic of those beggars. These at least can be identified through the micro-expression, sound pressure, and eye tracking. The analysis of the human’s track and physical fact through al-Quran here is what the authors intend as Quran forensic. Based on the distinguishing indicators from the analysis of the Quran forensic, this article found a new model for solving beggar problems with a multidisciplinary approach.